Breakdown Properties of Polyethylene Nanocomposites Containing Calcined Zirconia (ELEKTRIKA- Journal of Electrical Engineering, 2024)
Electrical insulation is vital in high voltage apparatuses. The most common materials used in commercial high voltage power cable insulation are polymers such as low-density polyethylene (LDPE) and cross-linked polyethylene (XLPE). Nevertheless, these insulation materials have their own advantages and disadvantages. The use of LDPE alone, for example, could not sustain high operating temperatures. Meanwhile, XLPE insulation has crosslinking byproducts that cause degradation of the material especially in the long run. Therefore, PE blends such as LDPE and HDPE blends have been proposed to exhibit material characteristics having good comprises. The composition of 80% LDPE and 20% HDPE often gives desirable results in the flexibility and dielectric properties of the material. Consequently, polymer nanocomposites have been proposed to enhance the performance of LDPE/HDPE blend power cable insulation materials. Although the addition of nanofillers to polymers can enhance the dielectric properties of nanocomposites, it can also otherwise degrade the dielectric properties of nanocomposites, especially the breakdown strength. The current work was conducted to investigate the effects of calcined zirconia (ZrO2) on the breakdown properties of polyethylene (PE) nanocomposites. The ZrO2 nanopowder used was uncalcined, calcined at 900 °C, and calcined at 1100 °C, to determine these effects on the breakdown strength of PE/ZrO2 nanocomposites. The results showed that PE/ZrO2 nanocomposites possessed similar breakdown strength to unfilled PE when ZrO2 was uncalcined and calcined at 900 °C. Nevertheless, calcining ZrO2 at 1100 °C led to a slight reduction in the breakdown strength of PE/ZrO2 nanocomposites compared to unfilled PE. This was ascribed to the agglomeration of ZrO2 upon calcining at 1100 °C. Therefore, nanofiller calcination temperatures had effects toward the breakdown strength of the final nanocomposites.
Keywords: breakdown; calcination; zirconia; polymers; nanocomposites